Analysis of Structural Strengths Applied the Cableway Group - Lates, Daniel; Alfianu, Calin (International Journal of Engineering and Management Sciences, 2023)
This paper will present the analysis of structural strengths for the cableway group. Three loading scenarios were analyzed. Each of these scenarios will be presented on the cableway group and explained with the intervening forces.